2016
DOI: 10.3813/aaa.918969
|View full text |Cite
|
Sign up to set email alerts
|

Microphone with Planar Nano-Gauge Detection: Fluid-Structure Coupling Including Thermoviscous Effects

Abstract: To cite this version:Thierry Verdot, Emmanuel Redon, Kerem Ege, Jaroslaw Czarny, Cécile Guianvarc'H, et al.. Microphone with planar nano-gauge detection: fluid-structure coupling including thermoviscous effects. Acta Acustica united with Acustica, Hirzel Verlag, 2016, 102 (3) AbstractThis article presents the modeling of a MEMS microphone with an original architecture formed of mechanical structures moving in the plane of the substrate. On the contrary of most microphones generally constituted of an oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is found that the volume of the back cavity is the most critical parameter that affects the sensitivity. [135,136] In a subsequent study, a 0.28 μm CMOS integrated circuit is implemented as the readout circuit together with an analog-to-digital converter (ADC) based on a 1-bit Sigma delta modulator. As a result, a noise density of 7 nV Hz À1/2 in the frequency range from 10 Hz to 10 kHz is achieved.…”
Section: Microphonesmentioning
confidence: 99%
“…It is found that the volume of the back cavity is the most critical parameter that affects the sensitivity. [135,136] In a subsequent study, a 0.28 μm CMOS integrated circuit is implemented as the readout circuit together with an analog-to-digital converter (ADC) based on a 1-bit Sigma delta modulator. As a result, a noise density of 7 nV Hz À1/2 in the frequency range from 10 Hz to 10 kHz is achieved.…”
Section: Microphonesmentioning
confidence: 99%
“…Note that such MEMS structures can be employed in other domains than audio, such as energy transfer, energy harvesters, and resonators [ 9 , 10 , 11 ]. However, new designs presenting technological advances have been proposed recently in the literature, such as a microphone with moving microbeam [ 12 ], or transducers (sources and microphones) with perforated moving electrodes. The mean motivation for the work presented herein is the latter case with electrodes in the form of elastic perforated plates clamped at all boundaries [ 13 ] or rigid elastically supported perforated plates [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coulomb-actuated microbeams play a crucial role in many Micro-Electro-Mechanical Systems (MEMS) applications [1][2][3] . They enable actuation using electrostatic forces and capacitive sensing, give rise to pioneering applications in medicine 4 , communications 5,6 , sensing 2,7 , and consumer products [8][9][10][11][12] . To meet the needs of recent developments, such as 5G Internet of Things (5G-IoT) 6 , augmented reality 13 , and Green ICT (information and communications technology) 14,15 , a system level consideration of a high number of electro-mechanical components is necessary.…”
Section: Introductionmentioning
confidence: 99%